Ethical dilemmas experienced by occupational therapy students â€" the reality - N NortjÃ©; J de Jongh (South African Medical Association, 2015)
Background. Ethics training strives to facilitate critical thinking, objective analysis and clinical reasoning skills to equip students with the abilityto make an impartial and unbiased decision in different contexts and diverse client populations. This enhances studentsâ€™ learning experiences.Occupational therapy (OT) students are expected to work in a variety of contexts. They experience many sources of conflict in their fieldwork practiceon a daily basis, while at the same time upholding professional values, responsibilities and duties.Objectives. To determine the issues that students face in their fieldwork practice and address these in an ethical manner.Methods. Qualitative research was done among fourth-year OT students by means of an open-ended questionnaire.Results. Three major themes relevant to ethical issues were identified: professional-student relationship; professional boundaries; and disclosureof information and keeping information confidential.Conclusion. The salient themes identified reflect the primary ethical tensions in the international literature from the UK and Canada, but little evidencehas been reported from South Africa. Taking cognizance of this, those who are involved in the training of healthcare professionals should incorporate theidentified issues in the class discussions. For many students their fieldwork practice may be their first experience with some of the aforementioned issues.Alluding to these in a safe environment (class situation) and equipping the students with a framework of analysis are very important.